إجماعات ابن دقيق العيد الفقهية في شرحه على عمدة الأحكام–كتاب الزكاة والصيام والحج أنموذجا- - خايف, حايف (University of Eloued جامعة الوادي, 2022)
يتجلى هدف هذا البحث الموسوم بــــــــ "إجماعات ابن دقيق العيد الفقهية في شرحه على عمدة الأحكام–كتاب الزكاة والصيام والحج أنموذجا-" في إحياء التراث الفقهي للفقهاء المتقدمين، وإبراز مكانتهم الفقهية والعلمية، ودورهم في خدمة العلم ونشره، ورغبتي في الاستفادة من الكنوز الفقهية المخبأة في كتاب إحكام الأحكام شرح عمدة الأحكام لابن دقيق العيد -رحمه الله-، ومعرفة طريقته في شرحه للأحاديث وعرضه للمسائل، وكيفية ذكره لإجماع الفقهاء في الكتب المذكورة، خاصة وأن هذا الكتاب من أهم كتب شروح عمدة الأحكام. وبعد هذا الجهد المتواضع استخرجت ثمانية إجماعات للفقهاء في كتابي الزكاة والصيام، وتسعة إجماعات في كتاب الحج ذكرها العلامة ابن دقيق العيد، حيث استعمل ألفاظا مختلفة للإجماع، كالتصريح بلفظ الإجماع، أو ذكر لفظ الاتفاق، أو التعبير بقوله: "لم يختلفوا، أو لا خلاف". The objective of this research, which is tagged with "The jurisprudential consensus of Ibn Daqiq al-Eid in his explanation on the pillar of provisions - the book of zakat, fasting and Hajj as a model -" is manifested in reviving the jurisprudential heritage of the advanced jurists, highlighting their jurisprudential and scientific status, their role in serving and spreading science, and my desire to benefit from the hidden jurisprudential treasures In the book, Ihkm al-Ahkam, the Umdat al-Ahkam explained by Ibn Daqiq al-Eid - may God have mercy on him - and his method of explaining hadiths and presented issues, and how he mentioned the consensus of scholars. After this humble effort, I extracted eight consensus of scholars in the two books of Zakat and Fasting, and nine consensus in the Book of Hajj mentioned by the scholar Ibn Daqiq Al-Eid, where he used different terms for consensus, such as declaring the word consensus, or mentioning the word agreement, or expressing by saying: “They did not disagree, or there is no disagreement.” ".
مقال
Keywords: الإجماع؛ ابن دقيق؛ الزكاة؛ الصيام؛ الحج